Jovens e adultos em escola especial para pessoas com deficiência intelectual: escolarização em debate - Almeida, Míriam Elena Cesar (2017)
This assignment has the goals to analyze the literacy condition of youth and adults, enrolled in the special school for intellectual disability and propose a reflexion about the educational purpose of the special school. The theoretical methodology basis looks at the Historical and Critical Pedagogy and its fundamentals. It has been investigated the literacy by ways of writing samples, produced from a list of words dictated by the researcher, the writing of their name and by oral questions about their knowledge of personal data, such as their full name and date of birth. The investigation was produced with students of two special schools, from a municipality located in the interior of the São Paulo state. The results show that the students enrolled for more than five years didn’t appropriate themselves of the system of alphabetical writing, necessary knowledge for learning and academical and social development. They also review that the special school doesn’t have a pedagogical planning that act in the promotion of knowledge and that demonstrate possibilities of advancement of those students. The research looks into offering elements for the analysis of a reality ruled in a model of philanthropic special education, in which will result in the school and social exclusion of private subjects of knowledge appropriation.